Characterization of AMCs Produced by Stir Casting Technique. Issue 1 (April 2021) - Saleem, M; Kumar raj, Nishant; kumar, Yogesh; Kumar, Pranav
Abstract: Stir casting is the simplest and cheapest method to manufacture composite materials. The objective of the research work is to produce Aluminum Matrix Composites with LM5 as matrix material and Fly Ash as reinforcement material at 0, 5, 10 % by weight, using stir casting technique and to study the mechanical properties such as tensile test, impact test, hardness test. The wettability between all these materials is assured by stir casting process. The microstructure of the composite show that the reinforcement material is homogeneously distributed in the matrix materials. Tensile Strength decreases with increase in weight percentage of Fly Ash. The weight percentage of Fly Ash has no effect on the impact strength of the composite. The hardness increases with the increase in weight percentage of fly ash and hence the fly ash can be used for increasing the wear resistance of the composites, where hardness plays a major role in industries which can turn industrial waste into industrial wealth.